Multiparametric ultrasound versus multiparametric MRI to diagnose prostate cancer (CADMUS): a prospective, multicentre, paired-cohort, confirmatory study. Issue 3 (March 2022) - Grey, Alistair D R; Scott, Rebecca; Shah, Bina; Acher, Peter; Liyanage, Sidath; Pavlou, Menelaos; Omar, Rumana; Chinegwundoh, Frank; Patki, Prasad; Shah, Taimur T; Hamid, Sami; Ghei, Maneesh; et al.
Summary: Background: Multiparametric MRI of the prostate followed by targeted biopsy is recommended for patients at risk of prostate cancer. However, multiparametric ultrasound is more readily available than multiparametric MRI. Data from paired-cohort validation studies and randomised, controlled trials support the use of multiparametric MRI, whereas the evidence for individual ultrasound methods and multiparametric ultrasound is only derived from case series. We aimed to establish the overall agreement between multiparametric ultrasound and multiparametric MRI to diagnose clinically significant prostate cancer. Methods: We conducted a prospective, multicentre, paired-cohort, confirmatory study in seven hospitals in the UK. Patients at risk of prostate cancer, aged 18 years or older, with an elevated prostate-specific antigen concentration or abnormal findings on digital rectal examination underwent both multiparametric ultrasound and multiparametric MRI. Multiparametric ultrasound consisted of B-mode, colour Doppler, real-time elastography, and contrast-enhanced ultrasound. Multiparametric MRI included high-resolution T2-weighted images, diffusion-weighted imaging (dedicated high B 1400 s/mm 2 or 2000 s/mm 2 and apparent diffusion coefficient map), and dynamic contrast-enhanced axial T1-weighted images. Patients with positive findings on multiparametric ultrasound or multiparametric MRI underwent targeted biopsies but were masked to their test results. If both tests yielded positive findings, the order of targeting at biopsy was randomly assigned (1:1) using stratified (according to centre only) block randomisation with randomly varying block sizes. The co-primary endpoints were the proportion of positive lesions on, and agreement between, multiparametric MRI and multiparametric ultrasound in identifying suspicious lesions (Likert score of ≥3), and detection of clinically significant cancer (defined as a Gleason score of ≥4 + 3 in any area or a maximum cancer core length of ≥6 mm of any grade [PROMIS definition 1]) in those patients who underwent a biopsy. Adverse events were defined according to Good Clinical Practice and trial regulatory guidelines. The trial is registered on ISRCTN, 38541912, and ClinicalTrials.gov, NCT02712684, with recruitment and follow-up completed. Findings: Between March 15, 2016, and Nov 7, 2019, 370 eligible patients were enrolled; 306 patients completed both multiparametric ultrasound and multiparametric MRI and 257 underwent a prostate biopsy. Multiparametric ultrasound was positive in 272 (89% [95% CI 85–92]) of 306 patients and multiparametric MRI was positive in 238 patients (78% [73–82]; difference 11·1% [95% CI 5·1–17·1]). Positive test agreement was 73·2% (95% CI 67·9–78·1; κ=0·06 [95% CI –0·56 to 0·17]). Any cancer was detected in 133 (52% [95% CI 45·5–58]) of 257 patients, with 83 (32% [26–38]) of 257 being clinically significant by PROMIS definition 1. Each test alone would result in multiparametric ultrasound detecting PROMIS definition 1 cancer in 66 (26% [95% CI 21–32]) of 257 patients who had biopsies and multiparametric MRI detecting it in 77 (30% [24–36]; difference –4·3% [95% CI –8·3% to –0·3]). Combining both tests detected 83 (32% [95% CI 27–38]) of 257 clinically significant cancers as per PROMIS definition 1; of these 83 cancers, six (7% [95% CI 3–15]) were detected exclusively with multiparametric ultrasound, and 17 (20% [12–31]) were exclusively detected by multiparametric MRI (agreement 91·1% [95% CI 86·9–94·2]; κ=0·78 [95% CI 0·69–0·86]). No serious adverse events were related to trial activity. Interpretation: Multiparametric ultrasound detected 4·3% fewer clinically significant prostate cancers than multiparametric MRI, but it would lead to 11·1% more patients being referred for a biopsy. Multiparametric ultrasound could be an alternative to multiparametric MRI as a first test for patients at risk of prostate cancer, particularly if multiparametric MRI cannot be carried out. Both imaging tests missed clinically significant cancers detected by the other, so the use of both would increase the detection of clinically significant prostate cancers compared with using each test alone. Funding: The Jon Moulton Charity Trust, Prostate Cancer UK, and UCLH Charity and Barts Charity.